COMMUNITY SERVICE ACTIVITIES COUNSELING IN MAKING WHO MP-ASI BASED ON LOCAL FOOD FOR POSYANDU CADRES AND BADUTA’ MOTHERS - Ariga, Reni Asmara; Nasution, Siti Saidah; Ariadni, Dwi Karina (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2018)
One effort to improve children's health and nutrition is to provide the best food for ages under two years (Baduta). If babies and children aged 6-24 months do not get enough nutrition from MP-ASI, it will cause disruption of growth and malnutrition. Medan Sunggal Health Center is one of the health centers in the fostered village of F.Kep USU. Based on the results of the toddler nutrition study conducted previously, there were still some nutritional problems, especially in the age group of Baduta. The main cause is the limited knowledge of mothers about Baduta nutrition and the skills of mothers in preparing food to meet nutritional needs with locally available food. Posyandu cadres who have been actively involved are still weak in providing breastfeeding and MP-ASI education. Even though Posyandu cadres are very potential their role as agents of change. Community service activities counseling for local food-based WHO MP-ASI for Posyandu cadres and baduta’ mothers was held on August 24, 2018, with the number of counseling participants thirty-five people. The end result is an increase in participants' knowledge and skills to shape good nutritional behavior in the family.